Artificial Intelligence In Digital Marketing Opportunities And Challenges - Eldon, Mokhamad; Sarita, Jena (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Artificial Intelligence (AI) technology has transformed the digital marketing sector, offering opportunities to increase efficiency, effectiveness, and personalization in marketing strategies. This article discusses the role of AI in digital marketing, focusing on the potential benefits it can bring and the challenges that arise during its implementation. Possessing the capacity to evaluate extensive datasets in real-time, AI enables companies to optimize customer experiences through more targeted personalization and automation of marketing processes. AI also facilitates consumer behavior prediction, more efficient advertising campaign management, and faster data-driven decision making. However, despite its many benefits, the adoption of AI in digital marketing also faces a number of significant challenges. Issues related to data privacy and the protection of consumers' personal information are of major concern, given that AI relies on extensive data collection and processing. In addition, the potential for algorithmic bias in AI systems can affect the accuracy and fairness of marketing decisions, which risks harming consumers and damaging a company’s reputation. The skills gap in AI adoption and the lack of adequate technological infrastructure are also barriers that need to be addressed, especially for small and medium-sized businesses. This study uses a literature approach to explore the challenges and opportunities that exist, and provides insights into strategies that organizations can use to manage and optimize the use of AI in digital marketing. The study emphasizes the importance of balancing the application of advanced technology with careful ethical management, with an emphasis on the importance of transparency, fairness, and sustainability in the use of AI. The results show that while AI offers great potential to support innovation and business growth, the successful implementation of this technology depends heavily on collaborative efforts between technology and skilled human resource management, as well as policies that support ethical governance